Sublethal exposure to deltamethrin impairs maternal egg care in the European earwig Forficula auricularia. (November 2020) - Meunier, Joël; Dufour, Juliette; Van Meyel, Sophie; Rault, Magali; Lécureuil, Charlotte
Abstract: The application of pesticides typically leads to lethal and sublethal exposure of non-target insects. Whereas our current understanding of these sublethal effects typically focuses on reproductive and physiological parameters, recent works emphasize that sublethal effects on behaviors such as maternal care could be of major importance in non-target species. However, it remained unknown whether these sublethal effects occur in insects. Here, we tested if exposure to sublethal doses of deltamethrin - a pyrethroid insecticide commonly used in crops - alters the expression of maternal egg care in females of the European earwig Forficula auricularia, a predator insect and pest control. Our results first reveal that deltamethrin exposure impaired the expression of three forms of maternal egg care: It decreased the likelihood of mothers to gather their otherwise scattered clutch of eggs, increased the time during which the female abandoned the clutch after a predator attack and reduced egg grooming duration. These sublethal effects did not reflect a lower activity of deltamethrin-exposed females, as these females increased their expression of self-grooming, and deltamethrin exposure did not affect females' exploration and mobility. Finally, we found that the negative effects of deltamethrin on egg care did not modify egg development, hatching rate and juvenile weight, possibly due to the transient effects of deltamethrin on maternal behaviors. Overall, our results reveal that sublethal exposure to a pesticide may diminish maternal egg care in a natural pest control and call for the integration of this measurement in assays on pesticides application. Highlights: This is the first test of pesticide effects on maternal care in an insect. We tested the impact of 4 sublethal doses of deltamethrin on earwig's behavior. Deltamethrin impaired 3 of the 6 measured forms of maternal egg care. Deltamethrin increased maternal self-grooming at the expense of egg-grooming. Deltamethrin did not affect female exploration, mobility and reproductive success.